Impact of Alien Networks on Consensus in a Team of Cooperative Mobile Robots - Ramos, Daniel C.; Moreno, Ubirajara F.; Oliveira, Luis; Almeida, Luis (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2015)
This work addresses the integration of a cooperative robot control strategy with a wireless network simulated with OMNeT++. We use a consensus control strategy in a rendez-vous task, which relies on sharing information among a group of robots simulated in a MANET environment. We consider WiFi ad-hoc technology with an overlay TDMA protocol, based on loose synchronization, to minimize message collisions within the team. Moreover we consider two topologies: a fixed pre-determined topology, which does not accept new links as robots come together, and a dynamic topology that creates new links as robots get within communication range. Then, the paper focuses on the impact that neighboring WiFi alien networks have on the control strategy for both topologies, due to the collisions they cause. We observe that having a well linked network generates better convergence results with the tradeoff of having an increased chance of divergence. Finally, we compare these results with those from a Matlab implementation of the control strategy using a typical simplified network model in which each message has a probability of being lost. The differences we observe reveal the importance of using a more accurate network model, as in OMNeT++, as well as the benefit of more complex topology control that avoids both weak links and high link density to increase resilience to alien networks.